Loise de Rosa, custode assagii della zecca di Napoli, dal tempo di Ladislao di Durazzo a quello di don Ferrante.: Loise de Rosa, Custodian assagii of the Mint of Naples, since Ladislas of Durace Time to don Ferrante - simonluca, perfetto (Aragón en la Edad Media, 2020)
Resumen: A través de un privilegio preservado en el Archivo de la Corona de Aragón ha sido posible no solo reconstruir algunos eventos de la vida de Loise De Rosa, autora de los Ricordi, sino también descubrir la existencia del oficio de guardián de los assaggi de oro, de plata y cobre hechos en ceca de Nápoles. También se reconstruyen las características institucionales de esta oficina, que fue ejercida por el De Rosa durante el reinado de tres reyes angevinos y dos aragoneses. Palabras clave: Loise De Rosa, ceca de Nápoles, guardián de los assaggi, Alfonso El Magnánimo, Corona de Aragón, Ricordi, siglo XV. Abstract: Through a privilege preserved in the Archive of the Crown of Aragon it was possible not only to reconstruct some events of the life of Loise De Rosa, author of the Ricordi, but also to discover the existence of the office of keeper of the golden assaggi, silver and copper made in the mint of Naples. Furthermore the institutional features of this office are reconstructed, also because De Rosa exercised it during the reign of three Angevin rulers and two Aragoneses. Keywords: Loise De Rosa, mint of Naples; keeper of the assaggi, Alfonso the Magnanimous, Crown of Aragon, Ricordi, 15th century.